Where Do Medical Students Look for Information? A Study on Scientific Consultation Sources in Peru - Moya-Salazar, Jeel (2022)
“Introduction: Scientific consultation sources is essential in the quality of information during medical training worldwide. The sources of consultation should provide quality information to students who begin with clinical courses; however, it is unknown how and where students seek data in all medical schools in Peru. In this study, we determine the most frequent sources of scientific consultation of medical students at Norbert Wiener University. Materials and methods: We conducted a survey-based observational study in 148 volunteers (mean age 22.1±5.4 years) during 2019. A 21-items questionnaire was divided into three components: demographic data (10 questions), scientific consultation sources (7 questions), and Information search engines (4 questions). Results: Eighty (54.1%) students were between 20-30 years, and 26.8% worked < 20 hours per week. The scientific search sources considered very usefully were scientific articles (75.4%) and specialized books (49.3%), while 33% did not know Medscape. Regarding audiovisual sources, documentaries on the history of medicine and YouTube were considered useful in 41% and 48%, respectively. We found differences in the use of consultation sources (p =0.031), Medscape (p =0.001), documentaries (p=0.009), and YouTube (p=0.022) among medical years. Sixty-three percent considered Wikipedia useful, and 19.3% used PubMed, while Google was the most frequent information search engine, followed of Scielo and Google scholar. We found a correlation between year of students and SciELO (p=0.024) and Google (p=0.024) engine use. Conclusions: Our results suggest that scientific articles, specialized books and audiovisual sources (documentaries and YouTube) were convenient for medical students. In addition, we have found that as students’ progress through the years in medical school, they make less use of rigorous scientific reference sources.“